Investigation of mine pressure and deformation due to phosphate ore body excavation based on Hoek-Brown model. (September 2016) - Wang, Tao; Zhao, Xianyu; Hu, Wanrui; Chen, Jinhua; Cheng, Long; Zhao, Lianzheng; Zheng, Hanzhong
Abstract: Phosphate ore body is an important basis for food supplies and the fine phosphorus chemical industry. With underground mining of the Ph3 seam of Xiongjia Gulf Phosphate ore stope in China as a research background, the excavation process is simulated using the Hoek-Brown model in this paper. Hoek-Brown parameter selection method is proposed first, and the influence of the goaf adjacent to this seam and the rock movement caused by underground mining, pillar yield and surface subsidence deformation are then studied. Finally, the feasibility of implementing a room-and-pillar mining system in the gently inclined phosphate ore body is analyzed. It is pointed out that local ground subsidence should cause enough attention.